198 Orthopaedic Trauma Services During A National Lockdown and Pandemic: Workload and Outcomes from A UK Major Trauma Centre. The Need for Continuing the Provision of Services. (4th May 2021) - Donovan, R; Tilston, T; Frostick, R; Chesser, T
Abstract: Aim: To review the trauma operating workload, theatre time and outcomes at a time of national lockdown and the beginning of the COVID-19 pandemic, comparing it with 2019. Method: A retrospective analysis at a single UK MTC. We included all patients undergoing emergency/urgent T&O surgery. Data collected included anatomical injury site, mechanism of injury, operative procedure, anaesthesia, theatre time, complications, and 30-day mortality. Results: 159 operations were performed on 142 patients in April 2019, and 110 operations on 106 patients in April 2020 (national lockdown). This led to a decrease of 30% due to reduced numbers from RTAs and sport-related injuries. Volumes of hip fractures and injuries from low-energy falls remained the same. Operative total theatre time increased by a mean of 14 minutes, and complications and mortality were not significantly changed. The incidence of COVID-19 in the patients tested was 8.5%, which matched the population incidence at the time. Conclusion: Orthopaedic trauma services must be maintained during a national lockdown. There is no decrease in the volume of patients sustaining falls, including hip fractures. Mean operating time only increases by 14 minutes with the wearing of PPE. This should be part of future planning of any pandemics or national lockdowns.